2017
DOI: 10.1016/j.jcms.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Facial thirds–based evaluation of facial asymmetry using stereophotogrammetric devices: Application to facial palsy subjects

Abstract: Many conditions can compromise facial symmetry, resulting in an impairment of the affected person from both esthetic and functional points of view. For these reasons, a detailed, focused, and objective evaluation of facial asymmetry is needed, both for surgical planning and for treatment evaluation. In this study, we present a new quantitative method to assess symmetry in different facial thirds, objectively defined on the territories of distribution of trigeminal branches. A total of 70 subjects (40 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 23 publications
1
42
0
5
Order By: Relevance
“…The introduction of modern 3D image acquisition and elaboration procedures allows the operators to perform more precise and complete analyses based on mirroring and registration techniques. This type of procedures have already been applied to the assessment of facial asymmetry, through the reconstruction of a midsagittal plane [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of modern 3D image acquisition and elaboration procedures allows the operators to perform more precise and complete analyses based on mirroring and registration techniques. This type of procedures have already been applied to the assessment of facial asymmetry, through the reconstruction of a midsagittal plane [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Acquisitions were obtained after the patients' written informed consent and did not involve any invasive, painful or dangerous procedure. All procedures were performed as previously described in the literature [12,13]. In brief, on each facial image, a set of 50 anthropometric landmarks were identified and digitized.…”
Section: Methodsmentioning
confidence: 99%
“…Ears were excluded too (Figure 1). The procedure is described in detail in a previous study performed by our group, and it was found to be repeatable [13]. For all the twin couples, the FAIs of the corresponding siblings were registered.…”
Section: Identification Of Facial Area Of Interest (Fai) and Facial Tmentioning
confidence: 99%
“…The aim of the current investigation is to evaluate differences and similarities on the superimposed facial thirds of couples of MZT acquired through stereophotogrammetry. An anatomic criterion, previously validated by our group, is used in the definition of the thirds [13]. Since the common genetic background of the MZT, the information obtained in this study can be of interest in assessing the respective influences by genes or environment on facial morphology.…”
Section: Introductionmentioning
confidence: 99%